HSV Esophagitis in an Immunocompetent 17-Year-Old - Vedika Rajasekaran BS; Victoria Rahaman MD; Xing Hou MD; Russell W. Steele MD (SAGE Publishing, 2021)
Herpes Simplex Virus (HSV) esophagitis is a relatively rare form of infectious esophagitis. Typically, patients with viral esophagitis are immunocompromised. HSV esophagitis in an immunocompetent patient is uncommonly reported. The objective of this case report is to discuss symptoms, investigations, imaging, and treatment of HSV esophagitis in a healthy adolescent male. A previously healthy 17-year-old male presented to the ED of our facility with a 5-day history of fever, odynophagia, lethargy, and 2 episodes of emesis that failed to resolve with antibiotic treatment. Investigations revealed a low platelet count, mild hyponatremia, hypochloremia, and an elevated AST and ALT. A respiratory infection panel as well as CMV IgG, HIV, Rickettsia, and EBV tests were negative. HSV-1 PCR was positive and upper endoscopy revealed a friable mucosa, erythema, and exudates in the lower esophagus and erythematous duodenopathy. The patient received a diagnosis of HSV esophagitis and was treated with a 14-day course of IV to PO acyclovir. There was a rapid improvement of his symptoms with antiviral therapy.